1981
DOI: 10.1056/nejm198101083040203
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Prostacyclin and Platelet Thromboxane A2after Low-Dose Aspirin

Abstract: To compare the inhibitory effects of aspirin on prostaglandin synthesized by vessel walls and platelets, we obtained vein segments from five subjects before they were given 150 or 300 mg of aspirin and at various intervals afterward. We then measured prostacyclin (PGI2) synthesis with a radioimmunoassay for its stable metabolite, 6-keto-prostaglandin F1 alpha. Platelet production of thromboxane A2 was measured with a radioimmunoassay for its stable metabolite, thromboxane B2. Two hours after aspirin had been g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
0
2

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(69 citation statements)
references
References 12 publications
4
63
0
2
Order By: Relevance
“…This hypothesis was regarded as unlikely in a previous paper [25], which showed that the levels of 6-oxo-PGFt~ (a by-product of prostacyclin) did not increase following DDAVP, and is conclusively ruled out in the present study. In fact, aspirin administered to a normal subject in a dose capable of inhibiting the synthesis of prostacyclin over 12 h before study [26], did not modify the platelet retention pattern following DDAVP.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This hypothesis was regarded as unlikely in a previous paper [25], which showed that the levels of 6-oxo-PGFt~ (a by-product of prostacyclin) did not increase following DDAVP, and is conclusively ruled out in the present study. In fact, aspirin administered to a normal subject in a dose capable of inhibiting the synthesis of prostacyclin over 12 h before study [26], did not modify the platelet retention pattern following DDAVP.…”
Section: Discussionmentioning
confidence: 83%
“…Further work is necessary to characterize this anti-adhesive mechanism(s). Prostacyclin, a potent anti-aggregating/anti-adhesive prostaglandin synthesized by the endothelial cells [26] could be released with vWF/VIII-RAG and inhibit platelet retention. This hypothesis was regarded as unlikely in a previous paper [25], which showed that the levels of 6-oxo-PGFt~ (a by-product of prostacyclin) did not increase following DDAVP, and is conclusively ruled out in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report from Sheffield, England has shown reduction of prostacyclin levels in the veins of subjects given different doses of aspirin. 9 It had been previously believed that if 300 mg of aspirin was given daily, only TXA 2 and not prostacyclin would be inhibited. If large doses, 900 mg, were given, both would be inhibited.…”
Section: Galal Ziady MDmentioning
confidence: 99%
“…The two most recently studied and described in detail are thromboxane, a plateletaggregating agent produced by thrombocytes, and prostacyclin or PGI-2, which is released by blood vessel walls and is a potent inhibitor of platelet aggregation. 8,9 The production or release of both of these factors is inhibited by aspirin, and it has been suggested that the administration of aspirin to men over the age of 20 and women over the age of 40, on a chronic, long-term basis, may lessen the severity of arterial thrombosis and arteriosclerosis. 10 This has been severely challenged in the literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation